The use of positive rest in maintaining the level of creatine phosphokinases enzyme and the peak and average non-oxygen capacity of Iraqi Premier League football players during the transitional period - Naser , ammar; Khalaf , Mohameed; Ali, Naji (Journal of Physical Education, 2024)
The importance of research has emerged through training during the transitional period and maintaining a certain level of physical and functional capabilities, highlighting the correct planning, and including the transitional period in the annual coach’s curriculum until football players reach advanced levels, through various exercises that are different from the main event practiced by the player, and with moderate intensity. As for the research problem, it was focused on the fact that there is a lack of focus by the coaches on the transitional period because they believe that it is outside the training season. This is what drives the player and the coach to start from scratch at the beginning of each new football season, due to the clear decline in the level of physical and functional performance. Therefore, the researcher decided to study this problem and develop appropriate solutions to it through various training for the transitional period and its impact on maintaining the level of some physical and functional capabilities of the Iraqi Premier League players in football.